A Discourse Analysis of Social Media Voices in #Release Thirumurugan - Prakash, M; L, Ramalakshmi (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Article 19 of the Indian constitution lays down that all citizens shall have the right to freedom of speech and expression, to assemble peacefully, and without arms, to form associations or unions, to move freely throughout the territory of India, to reside in any part of the territory of India, to acquire hold and dispose of property and to practice any profession or to carry on any occupation, trade or business. The arrest of Thirumurugan Gandhi, amongst many, is an example of Govern mentality in our state. Freedom of Speech and Expression is guaranteed in our democratic society. The advent of social media has greatly contributed to the possibility of being heard to a great extent, giving voice to the public. From mere opinions to strong points, social media serves as an accessible medium of the citizens. The arrest of Thirumurugan Gandhi, Human rights activist, garnered widespread social media attention through hashtag #Release Thirumurugan. This research is an exploratory attempt that aims to understand how online users are using Facebook and Twitter to spearhead the release of Thirumurugan Gandhi. In the light of Foucault’s concept of Governmentality, this research uses discourse analysis to analyse posts in #Release Thirumurugan. The overall sentiment expressed through the Facebook posts and tweets favour the release of Thirumurugan Gandhi. The mushrooming and viral nature of social media is contagious and has the scope to build a revolution. More the suppression of voices, activism would intensify further. How to cite this article: Prakash M, Ramalakshmi L. A Discourse Analysis of Social Media Voices in # Release Thirumurugan. J Adv Res Jour Mass Comm 2018; 5(4): 160-163. DOI: https://doi.org/10.24321/2395.3810.201833